Ubiquitin‐like domains can target to the proteasome but proteolysis requires a disordered region - Yu, Houqing (EMBO J, 2016)
Ubiquitin and some of its homologues target proteins to the proteasome for degradation. Other ubiquitin‐like domains are involved in cellular processes unrelated to the proteasome, and proteins containing these domains remain stable in the cell. We find that the 10 yeast ubiquitin‐like domains tested bind to the proteasome, and that all 11 identified domains can target proteins for degradation. Their apparent proteasome affinities are not directly related to their stabilities or functions. That is, ubiquitin‐like domains in proteins not part of the ubiquitin proteasome system may bind the proteasome more tightly than domains in proteins that are bona fide components. We propose that proteins with ubiquitin‐like domains have properties other than proteasome binding that confer stability. We show that one of these properties is the absence of accessible disordered regions that allow the proteasome to initiate degradation. In support of this model, we find that Mdy2 is degraded in yeast when a disordered region in the protein becomes exposed and that the attachment of a disordered region to Ubp6 leads to its degradation.